Arsenene Nanodots with Selective Killing Effects and their Low‐Dose Combination with ß‐Elemene for Cancer Therapy (Adv. Mater. 37/2021). Issue 37 (14th September 2021) - Liu, Chuang; Sun, Shan; Feng, Qiang; Wu, Gongwei; Wu, Yiting; Kong, Na; Yu, Zhangsen; Yao, Junlie; Zhang, Xingcai; Chen, Wei; Tang, Zhongmin; Xiao, Yufen; et al.
Abstract : Arsenical Drugs In article number 2102054, Aiguo Wu, Tian Xie, Wei Tao, and co‐workers reveal PEGylated arsenene nanodots (AsNDs@PEG) with high monoelemental arsenic purity and negligible systemic toxicity as a new‐concept arsenical drug. This AsNDs@PEG, when applied in a low‐dose combination strategy with β‐elemene, a plant‐derived anticancer drug, achieves synergistic therapeutic outcomes.